Adhesive deformation dynamic processes in boundary layers. Message IV. Physical adhesive and hydrodynamic (AHD) model of the friction and management of working capacity tribosistem in the conditions of boundary greasing - Стельмах, А.У. (Problems of Tribology, 2014)
Firstly the arising of different polarity of gradient pressure on both sides of the transition contact region as well as localization of adhesive interaction of surfaces in diffuser area has been established on the base of complex systematic researches of dynamic processes in a boundary layer (DPBL) and its properties in all areas of tribology contact the sliding bearing. Dynamic and deformation processes, effects of warm- and mass-transfer, turbulence, kinetics of of oil-steam-air mix formation, layer structure, interaction of surfaces, etc. in interrelation with tribology characteristics have been determined. The physical adhesive-hydrodynamic (AHD) friction model has been developed. AHD model eliminates contradictions between adhesive-deformation and elasto-hydrodynamic approaches to the description of processes of boundary friction and allows to develop original control methods of tribosystem working capacity. These methods are confirmed by full-scale tests. Using generalized AHD model, the perspective devices of different function have been developed that are confirmed by patents and passed laboratory, bench and operational tests.